Green Entrepreneur Learning Strategy in Strengthening Environmental Care Character for Sustainable Living - Handayani, Trisni; Ramadhani, Anindita (International Journal of Learning Reformation in Elementary Education, 2025)
Environmental care character education is one of the main foundations of living a sustainable lifestyle, especially for future educators who will work as social change agents. Examining green entrepreneurial learning techniques as a novel approach to assisting students by fostering environmental care values in the elementary school teacher education study program participants is the aim of this study. Students' ecological knowledge, feeling of social responsibility, and ability to think critically about environmental concerns may all be enhanced by introducing green entrepreneurship concepts into the curriculum, according to observations. Among the strategies employed are project-based learning (PjBL), multidisciplinary collaboration, and strengthening sustainability principles in all entrepreneurial undertakings. Methods: This research is descriptive and quantitative. The data analysis from expert validation results yielded an average score of 91, indicating exceptionally valid. The study's subjects were 112 pupils. Techniques for analyzing data that employ inferential statistics. Effectiveness testing is done using the analytical requirements test. The results show that this method not only shapes students' concerns about the environment but also inspires them to take an active role in developing creative, environmentally responsible solutions. According to this conclusion, the idea of green entrepreneurs should be more widely integrated into education in order to improve the nature of environmental care, which suggests that doing so will support sustainable development.